Impactos eclesiológicos do “Filioque” - Lepargneur, Hubert (Revista Eclesiástica Brasileira, 2003)
Os esforços ecumênicos travados entre as Igrejas Ortodoxas e a Igreja Latina chocam-se ainda com a diversidade de suas eclesiologias, apesar da considerável herança cristã comum e dos recentes e conhecidos esforços de João Paulo II. Este artigo tenta esclarecer a contribuição que teve e tem a recepção ou a recusa do Filioque nestas diferenças eclesiológicas. O patriarcado bizantino está mais tolerante, mas o patriarcado russo opõe ao Vaticano o princípio de que num dado território só pode haver uma única Igreja cristã, tornando chocante a criação de novas dioceses em território tradicionalmente ortodoxo; será que a eclesiologia do Filioque tem algo a ver com isso? Abstract: The ecumenical efforts made by the Orthodox and Latin Churches are still finding an obstacle in the diversity of their ecclesiologies, in spite of a considerable common Christian heritage and of Pope John Paul the Second’s well-known recent efforts in this direction. This article attempts to clarify the contribution made and still being made to these ecclesiological differences by an acceptance or refusal of the Filioque. The Byzantine Patriarchate is more tolerant, but the Russian Patriarchate is against the Vatican in that it advocates the principle that, in a given territory, there can be only one Christian Church; this makes the creation of new dioceses in traditionally orthodox territories an offensive act; is it possible that the Filioque ecclesiology has anything to do with this?